2020
DOI: 10.3390/land9120495
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Impact of Urban Planning Concepts on Reducing the Urban Sprawl of Ulaanbaatar City Using Certain Spatial Indicators

Abstract: The urban sprawl process of Ulaanbaatar has changed dramatically due to population growth. Ulaanbaatar city land management master plan defined the settlement zone area suitable for living as 33,698 ha. However, due to unrestricted urban sprawl caused by the exponential growth of the city’s population, the settlement zone area reached 39,235 ha, which exceeds the limit by 5537 ha. In order to tackle this issue, several urban planning concepts were developed to be implemented within Ulaanbaatar city urban plann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Appiah et al claimed that the increased demands for new housing and good accessibility to new extensions are the most important factors in Bosomtwe, Ghana [17]. Batsuuri et al argued that urban planning policy is the main factor behind urban expansion in Ulaanbaatar city, Mongolia [18]. Ju et al found that the distance to the downtown area is the most influential factor in Beijing, China [19].…”
Section: Introductionmentioning
confidence: 99%
“…Appiah et al claimed that the increased demands for new housing and good accessibility to new extensions are the most important factors in Bosomtwe, Ghana [17]. Batsuuri et al argued that urban planning policy is the main factor behind urban expansion in Ulaanbaatar city, Mongolia [18]. Ju et al found that the distance to the downtown area is the most influential factor in Beijing, China [19].…”
Section: Introductionmentioning
confidence: 99%
“…In many parts of the world, urban sprawl can have a significant impact on the quality of life. As a result, developments in urbanization and their magnitude should be regularly observed [5]. Then, it can be possible to control the urbanization process and create sustainable developments [6].…”
Section: Introductionmentioning
confidence: 99%